Imaging the postoperative patient: long-term complications of gastrointestinal surgery - Ramos-Andrade, Daniel (2016)
Objectives The objectives of this review are (1) to become acquainted with the long-term complications of surgery of the gastrointestinal tract, and (2) to appreciate the appropriate use of imaging in the assessment of long-term complications. Background Gastrointestinal tract surgery comprises a group of procedures performed for a variety of both benign and malignant diseases. In the late postoperative setting, adhesions and internal hernias are the most important complications. and they can be further complicated by volvulus and ischemia. At present, computed tomography (CT) is the workhorse for evaluating late postoperative complications. Accurate imaging assessment of patients is essential for adequate treatment planning. Imaging findings or procedure details In this pictorial essay we will review the most frequent long-term complications after gastrointestinal surgery, including adhesions, afferent loop syndrome, closed-loop obstruction, strangulated obstruction, internal hernias, external hernias, anastomotic strictures and disease recurrence. Examples will be depicted using iconography from the authors’ imaging department. Conclusions Knowledge of the most frequent complications after gastrointestinal surgery in the late postoperative period is of paramount importance for every radiologist, so that potentially life-threatening situations can be promptly diagnosed and adequate therapy can be planned.